"Down the drain": carbapenem‐resistant bacteria in intensive care unit patients and handwashing sinks. Issue 5 (18th March 2013) - Kotsanas, Despina; Wijesooriya, W R P L I; Korman, Tony M; Gillespie, Elizabeth E; Wright, Louise; Snook, Kylie; Williams, Natalie; Bell, Jan M; Li, Hua Y; Stuart, Rhonda L
Abstract: Objectives: Clinical utility of carbapenem antibiotics is under threat because of the emergence of acquired metallo‐β‐lactamase (MBL) genes. We describe an outbreak in an intensive care unit (ICU) possibly associated with contaminated sinks. Design, setting and participants: Four clusters of gram‐negative bacteria harbouring the MBL gene bla IMP‐4 were detected in the ICU at Dandenong Hospital between November 2009 and July 2012. Epidemiological investigations were undertaken in order to identify a common point source. During September 2012, screening using rectal swabs for all ICU patients, and environmental swabs targeting all ICU handwashing sinks and taps were collected. Samples were cultured onto selective carbapenem‐resistant Enterobacteriaceae (CRE) agar. Suspected CRE isolates were further characterised using the modified Hodge test and VITEK 2 and confirmed by polymerase chain reaction and sequencing of MBL genes. Clinical and environmental CRE isolates were typed by pulsed‐field gel electrophoresis. Results: Ten clinical isolates and one screening isolate of CRE (consisting of Klebsiella pneumoniae [5], Serratia marcescens [4], Enterobacter cloacae [1] and Escherichia coli [1]) were detected with the bla IMP‐4 gene over the 30‐month period. S. marcescens was isolated persistently from the grating and drain of eight central sinks. Molecular typing confirmed that clinical and environmental isolates were related. Tap water cultures were negative. Several attempts to clean and decontaminate the sinks using detergents and steam cleaning proved unsuccessful. Conclusion: This report highlights the importance of identification of potential environmental reservoirs, such as sinks, for control of outbreaks of environmentally hardy multiresistant organisms.